Health care system’s and health self-evaluation of Latvia inhabitants in the context of the European quality of life survey (EQLS) of 2011 and 2016 - Kristapsone, Silvija (University of Latvia, 2020)
The quality of the inhabitants of the country is a decisive factor influencing production. At the same time one of the factors characterizing the quality of the inhabitants is their health. Researches of scientists in the last decades have proved mutual interrelation of health of the inhabitants and economic growth: a healthy nation is an important factor of economic growth and vice versa, i.e., the economic growth improves the inhabitants’ health improving life quality in total. The subjective evaluation of the life quality supplements the official statistical information. The European Quality of Life Survey (EQLS) is an approved quality supervision and analysis tool that has taken place for the 4th time in 2016 and includes evaluation of the health care system, the inhabitants’ awareness of their health situation and mental well-being. The aim of the article is to assess the changes in separate indicators of health of Latvia society in the context of the European Union countries in the EQLS in 2016 in comparison with the survey in 2011. To achieve the aim the following tasks were forwarded: 1) to offer insight in the present understanding of the concept of society’s health and problems; 2) to analyse the EQLS 2016 data contrasting them with the data in Latvia and the EU in total. Descriptive and indicative statistical methods for analyses were applied in the research. As informative sources of inhabitants the European Life and Work conditions improvement fond in 2011-2012 and 2016 from the UK Archive, as well as the data of the World Bank, the World Health organization and Latvia Statistical directorate were used. As confirmed by the data of 2016 according to self-evaluation of respondents in total the healthcare quality in the EU has increased from 6,07 to 6,18 and this increase must be considered as statistically significant. In Latvia statistically insignificant decrease of the quality of the healthcare from 5,13 to 5,01 can be seen (European Foundation for the Improvement of Living and Working Conditions, 2018). In Latvia the inhabitants’ awareness of personal health condition (In general, how is your health?) has been evaluated as average while the average showing in the EU – as good. Latvia respondents the following statements (how you have been feeling over the last two weeks) about the last two weeks “I have felt cheerful and in good spirits”, “I have felt calm and relaxed”, “I have felt active and vigorous”, “I woke up feeling fresh and rested”, “my daily life has been filled with things that interest me” estimate more positively. At the same time “I have felt lonely” and “I have felt particularly tense” and “ I have felt downhearted and depressed “ are valued more negatively in 2016 in comparison with 2011, but it is statistically insignificant. However, it gives evidence about the increase of everyday life intensity, tension and stress, unfavourable conditions for mental and psychic health and the demand for immediate reaction.
Keywords: Health; Health indicators; Health care system; Research Subject Categories::SOCIAL SCIENCES::Business and economics